Style Leadership and Job Satisfaction to Performance Officer Through Organizational Commitment - fadliari bastian; Muh Yunus Amar (Scientia Integritas Utama, 2023)
In public groups, subordinates paintings constantly depending at the leader. If the leader does now not have the capacity to steer, very complicated responsibilities cannot be achieved properly. An company wishes an powerful leader, who has the capacity to persuade the behavior of its participants or subordinates. what's the relationship among style leadership and process delight on performance officer via variables organizational commitment? There are still few researchers who discover this query. This study aims to determine and analyze the effect of leadership style and job satisfaction on employee performance through organizational commitment. The type of data in this research is quantitative data. The primary data used is in the form of questionnaire results obtained from civil servants and honorary employees at the Hospital. Data were analyzed using quantitative analysis through path analysis, using the Amos program. The results of the study show that leadership style and job satisfaction have a direct positive and significant effect on organizational commitment. Leadership style and job satisfaction have a direct positive and significant effect on employee performance. And there is a significant indirect effect between leadership style and job satisfaction on employee performance through organizational commitment.